The Aboriginal past : contemporary perspectives - Critchett, Jan.; Ludwig, Wendy, 1957-; Deakin University. Faculty of Humanities. Open Campus Program (Geelong, Vic. : Deakin University, 1992)
Prepared for unit HUA814 offered by the Faculty of Humanities in Deakin University's Open Campus Program.
Includes bibliographical references.
Keywords: Aboriginal Australians -- History